Proteomic profiling reveals the potential mechanisms and regulatory targets of sirtuin 4 in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced Parkinson’s mouse model - Weng, Huidan; Song, Wenjing; Fu, Kangyue; Guan, Yunqian; Cai, Guoen; Huang, En; Chen, Xiaochun; Zou, Haiqiang; Ye, Qinyong (Frontiers in Neuroscience, 2023)
Parkinson's disease(PD), as a common neurodegenerative disease, currently has no effective therapeutic approaches to delay or stop its progression. There is an urgent need to further define its pathogenesis and develop new therapeutic targets. An increasing number of studies have shown that members of the sirtuin (SIRT) family are differentially involved in neurodegenerative diseases, indicating their potential to serve as targets for therapeutic strategies. Mitochondrial SIRT4 possesses multiple enzymatic activities, such as deacetylase, ADP ribosyltransferase, lipoamidase, and deacylase activities, and exhibits different enzymatic activities and target substrates in different tissues and cells; thus, mitochondrial SIRT4 plays an integral role in regulating metabolism. However, the role and mechanism of SIRT4 in PD are not fully understood. This study aimed to investigate the potential mechanism and possible regulatory targets of SIRT4 in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mice. The expression of the SIRT4 protein was found to be altered both in the MPTP-induced PD mouse mice and DJ-1KO rats. Following viral transfection of SIRT4 and quantitative proteomics, we identified 5094 altered proteins in the vitro model, including 213 significantly upregulated proteins and 222 significantly downregulated proteins. The results from GO annotation, COG/KOG classification, GO enrichment analysis, KEGG enrichment analysis, protein‒protein interaction (PPI) network analysis, and gene set enrichment analysis (GSEA) indicated that SIRT4 mainly affected the ribosomal pathway, propionate metabolism pathway, peroxisome proliferator-activated receptor (PPAR) signalling pathway and peroxisome pathway in cells, and we screened 25 potential molecular targets. Subsequent viral transfection and reverse transcription quantitative PCR (RT-qPCR) assays revealed that only fatty acid binding protein 4 (FABP4) in the PPAR signalling pathway was regulated by SIRT4 among the 25 molecules. Importantly, the alterations in FABP4 and PPARγ were verified in the MPTP-induced PD mouse model. In conclusion, our results indicated that FABP4 in the PPAR signalling pathway is the most promising molecular target of SIRT4 in an MPTP-induced mouse model and revealed the possible functional role of SIRT4. This study provides a reference for drug development and mechanism research with SIRT4 as a target or biomarker.